The Effect Of Multiple Intelligence-Based Guided Inquiry Learning On Social Skills Of Elementary School Students - Sri Hartatik; Galih Istiningsih; Seprtiyati Purwandari (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
This study aims at determining the effect of guided inquiry model based on multiple intelligence toward the social skills of elementary school students at Pasuruhan 1 State Elementary School, Mertoyudan District, Magelang Regency in Social Science learning of fourth grade. This research belongs to a Quasi-Experimental Design research with the Non-equivalent Control Group Design model. Research subjects were selected by Non-probability Sampling with saturation sampling model. The samples were 30 students consisting of 15 students in the experimental group and 15 students in the control group. The data collection methods were done by using a questionnaire and observation of social skills. The validity test of social skills questionnaire was done by using the product moment formula while the reliability test was done by using Cronbach Alpha formula with the help of the SPSS for windows version 25 program. Data analysis used in this research is a non-parametric statistical technique, namely the Mann-Whitney. The result of this study indicates that there is an effect of guided learning based on multiple intelligences on the social skills of elementary school students. This is proved by the results of the Mann-Whitney test analysis which shows the Asymps value. Sig. (2-tailed) of 0.003 < 0.05. By this result, it can be concluded that the hypothesis is accepted. Therefore, it can be said that there is social skills difference of the experimental class and the control class students. It is proved by a significant difference thus it shows that guided inquiry learning has a positive effect on student's social skills